Apical and lateral accuracy of intraradicular impressions made using the indirect and direct technique at three different locations: A comparative in vitro analysis - Godwin Clovis Da Costa; Praveen Rajagopal; Meena Ajay Aras; Amanda Nadia Ferreira (Wolters Kluwer Medknow Publications, 2024)
Background: There is limited literature available comparing the accuracy of intraradicular impressions made with a novel hybrid impression material using the indirect and direct technique at three different locations. Materials and Methods: For this comparative in vitro analysis, postspace was prepared in 15 recently extracted teeth and impressions made with vinyl polysiloxane, polyether (PE), vinyl polyether silicone (VPES), and pattern resin. Postpatterns obtained were re-seated on the teeth and longitudinally sectioned. A binocular microscope was used to measure apical and lateral discrepancies at three locations (L1, L2, and L3). L1 at the postcore junction, L2 at the middle of the post space, and L3, 2 mm short of the apical end. The data obtained were statistically analyzed using the Statistical Package for the Social Sciences (SPSS) software. One-way analysis of variance (ANOVA) (intergroup) followed by Tukey's post hoc test with P ≤ 0.05 was used. Results: The one-way ANOVA noted a highly significant difference at the apical location. Pattern resin had the highest apical discrepancy (151.93 ± 8.59 µm), whereas the lowest was with vinyl PE silicone (140.31 ± 11.46 µm). At L1, the highest discrepancy was seen with pattern resin (32.09 ± 2.31 µm), whereas the lowest was with the addition silicone (31.94 ± 2.54 µm). At L2, addition silicone (32.88 ± 2.81 µm) showed the highest discrepancy, whereas the lowest was with vinyl PE silicone (30.5 ± 8.79 µm). The PE group had the highest mean at the L3 location (31.38 ± 3.46 µm) and the lowest was with vinyl PE silicone (30.93 ± 2.25 µm). At all lateral locations, no significant difference was noted. Tukey's post hoc comparison showed a significant difference between pattern resin and VPES (11.62 µm) followed by pattern resin and addition silicone (11.47 µm) apically. Conclusion: The indirect technique using VPES or addition silicone is more accurate than the direct technique at the apical location.